Sense, Rhythm and Rhyme in Finnish Translations of Schlager Songs - Kehusmaa, Annu-Tuulia (My University, 2025)
Song translation is an interdisciplinary field which combines the research of music and translation. In this study, I examine three of the five aspects of the Pentathlon Principle by Low (2005): sense, rhythm and rhyme. The aim of this study is to examine how Finnish schlager translations balance between these three aspects, and how the prioritization of one aspect affects the translation of the other two. This is accomplished with the comparison of ten English songs and their Finnish translations. The results indicate that in the translation of schlager songs, rhythm and rhyme are restrictive aspects, and the translation of sense allows more variation. However, most of the songs primarily retain the meaning of the original, disclosing one song. In the translation of rhythm, the original number of syllables was followed in most parts, but each translation had from one to nine lines that had one or two syllables less or more than the original. The translation of rhyme also follows the original in most translations. The end rhyme pattern of the original is followed in at least one verse or chorus of the translations, and where it is not followed, the translations most often have more rhymes than the original. The retaining of the rhyme patterns and the creation of lots of end rhymes restricts which words can be used in each line, which complicates the following the original meaning. Therefore, the translation of sense requires stretching of the original meaning.
Keywords: Song translation, schlager songs, the Pentathlon Principle